Conviviality in entrepreneurial communities: main results from an exploratory research - Guercini, Simone; Milanesi, Matilde; Ranfagni, Silvia (Piccola Impresa / Small Business, 2020)
<span style="line-height: 105%; font-family: 'Arial','sans-serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The present study investigates conviviality, as related to social capital, in entrepreneurial communities and how it makes social relationships a context for developing business relationships and recognizing entrepreneurial opportunities. The methodology adopted includes both qualitative (indepth interviews, case analysis) and text-mining techniques for the analysis of qualitative data. The empirical research is based on emblematic cases of Italian entrepreneurial communities from the textile-clothing industry, located in Italy and China. The study sheds light on the mechanisms (from social to business relationships) that conviviality can trigger and the drivers of these mechanisms. The potentials and limits in using of conviviality for entrepreneurial activities are highlighted at the end of the paper.